HERMENEUTIKA HADĪṠ DALAM PEMIKIRAN MUHAMMAD MUSTAFA AL ‘AẒAMI - Zainal Abidin; Ahmad Majidun (SEKOLAH TINGGI AGAMA ISLAM AL-HUSAIN MAGELANG, 2021)
The writing basically wants to prove that 'Aẓami is substantially doing hermeneutic work. The hadīṡ 'Aẓami study method, both sanad and matan will be drawn in the discussion of hadīṡ hermeneutics, in which case the author uses three basic elements in hermeneutical discourse, namely the author (narrator), the text (hadīṡ) and the reader ('Aẓami). The purpose of this writing is to find out how hadīṡ hermeneutics in the Thoughts of Muhammad Mustafa> Al 'Aẓami. The writing method uses a literature review for 'Aẓami's works, namely Studies on Early Hadīṡ Literature (Hadīṡ Nabawi and the History of Codification) and Studies on Methodology and hadīṡ Literature as primary sources. In addition to these primary sources, the author also uses secondary sources in the form of works related to writing problems. The data analysis uses a technique in the form of content analysis. The results of the analysis show that 'Aẓami, in her hermeneutical work, uses several methods, namely 1) Comparison between hadīṡ-hadīṡ of Various Translators' Disciples. 2) Comparison of Statements from Narrators After a Certain Period. 3) Comparison between Written Documents and Conveyed from Memorize. 4) Comparison of Hadīṡ with Qur'anic Verses and 5) Rational Approach in Criticism of hadīṡ